Two New Hemoglobin Variants: Hb Tallahassee [α3(A1)Ser→Tyr; HBA2: c.11C>A] and Hb Madison-NC [β119(GH2)Gly→Ser; HBB: c.358G>A]. (June 2014) - Kutlar, Ferdane; Unguru, Yoram; Dixon, Natalia; Patel, Niren; Bailey, Lakiea; Zhuang, Lina; Carmichael, Harris; Kutlar, Abdullah
Abstract Of the 1570 reported hemoglobin (Hb) variants detected to date, 390 are α2-globin chain (some variants have yet to be identified by DNA analyses and are therefore presumed) and 827 are the result of mutations of the β-globin chain. Due to their location on the Hb structure, only a minority of these variants result in a clinical phenotype; most are silent and are detected during routine surveillance, are found incidentally during other disease-related investigations or following newborn screening programs. In this report we discuss phenotype/genotype and molecular characteristics of two new Hb variants, both of which were clinically silent. One is an α2-globin chain variant located at codon 3 [α3(A1)Ser→Tyr; HBA2: c.11C > A] named Hb Tallahassee and the other is a β-globin chain variant located at codon 119 [β119(GH2)Gly→Ser; HBB: c.358G > A] called Hb Madison-NC.